2012
DOI: 10.1007/s00426-012-0455-7
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the time course of inter-trial feature priming in singleton search

Abstract: Current theories of the locus of inter-trial priming effects in efficient visual search posit an early perceptual component that reflects the short-term influence of a memory trace for low-level stimulus attributes. Despite the fact that this memory trace is hypothesized to be short term, and should therefore have a diminishing influence on performance over time, there has been relatively little study of the effect of time alone on singleton priming effects. The present series of experiments addresses this iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The feature-weighting view is intuitive, and the idea that trials can produce ‘lingering’ activity that affects subsequent performance is supported by several neurophysiological findings (Kristjánsson and Campana, 2010; Yeung et al, 2006; de Lange et al, 2013). Similarly, the idea that such weighting is subject to decay is in line with the observation that facilitation effects have been found to rapidly disappear over the course of some 5–8 trials (Maljkovic and Nakayama, 1994; Hillstrom, 2000), and that long intertrial intervals can attenuate or abolish priming effects (Maljkovic and Nakayama, 2000; Thomson and Milliken, 2012). Note that different properties of a search trial might independently contribute to priming effects: most notably, repetitions of the response, position, and target-defining feature on a search trial might independently produce repetition benefits or switch costs (Meeter and Olivers, 2006; Lamy et al, 2010; Tollner et al, 2008; Gokce et al, 2014).…”
Section: Introductionmentioning
confidence: 56%
“…The feature-weighting view is intuitive, and the idea that trials can produce ‘lingering’ activity that affects subsequent performance is supported by several neurophysiological findings (Kristjánsson and Campana, 2010; Yeung et al, 2006; de Lange et al, 2013). Similarly, the idea that such weighting is subject to decay is in line with the observation that facilitation effects have been found to rapidly disappear over the course of some 5–8 trials (Maljkovic and Nakayama, 1994; Hillstrom, 2000), and that long intertrial intervals can attenuate or abolish priming effects (Maljkovic and Nakayama, 2000; Thomson and Milliken, 2012). Note that different properties of a search trial might independently contribute to priming effects: most notably, repetitions of the response, position, and target-defining feature on a search trial might independently produce repetition benefits or switch costs (Meeter and Olivers, 2006; Lamy et al, 2010; Tollner et al, 2008; Gokce et al, 2014).…”
Section: Introductionmentioning
confidence: 56%
“…Note that the color representation held in memory for participants in the imagery group may have been maintained in memory up until the point at which the following visual search display appeared. In contrast, the prior target representation in memory for the control group may have decayed passively over the 2-s intertrial interval (Brascamp, Pels, & Kristjansson, 2011; Martini, 2010; Thomson & Milliken, 2013), as there was no requirement to retain that representation over the intertrial interval. Thus, holding a color representation in an active state across the intertrial interval in the imagery groups may have increased the cost associated with disengaging attention following an erroneous shift of attention to a distractor (see Olivers, Peters, Houtkamp, & Roelfsema, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present work are important in several ways: (1) while there are now numerous demonstrations that attention capture effects are modulable by explicit, top-down knowledge and strategy, only one other study (to our knowledge) has demonstrated that such effects are sensitive to implicit context-specific knowledge (Cosman and Vecera, 2012); (2) Behavioral effects in several other performance domains have been shown to be modulated by the match or mis-match in task irrelevant contextual information between prior experience and current perception (i.e., proportion congruency effects in the Stroop task—Crump et al, 2006; negative priming effects—Neill, 1997; conflict adaptation effects—Spapé and Hommel, 2008; long-lasting inhibition of return—Wilson et al, 2006; and long-lasting priming effects in singleton search—Thomson and Milliken, 2012, 2013a,b). The present work however, represents the first evidence that properties of the task-relevant stimuli themselves can bias search behavior in the context of the attention capture paradigm; and (3) While most prior studies showing that prior experience can bias the capture of attention by an irrelevant singleton can be explained via automatic, trial-to-trial influences (i.e., the operation of “short-term” priming), the ISPC effect observed here demonstrates that trial history beyond the most recent experience can affect the capture of attention by the most salient item in the search display.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that the speed with which singleton search unfolds depends on whether the features of the target match those in the most recent contextually similar trial (Thomson and Milliken, 2012, 2013a). Additionally, when many prior experiences are contextually similar to the current one, priming effects are dependent on the number of intervening experiences that occurred between the current and “influencing” trial, which has been interpreted by some as evidence for a form of retrieval interference (Thomson and Milliken, 2013b; Experiment 3). It has also been shown that the benefits and costs of target feature repetitions and alternations vary depending on whether one is in a search context in which target repetitions are likely or unlikely (Geyer and Müller, 2009; Thomson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%